2016
DOI: 10.12776/ams.v22i1.627
|View full text |Cite
|
Sign up to set email alerts
|

Surface State Effect of Welded Stainless Steels on Corrosion Behavior

Abstract: <p style="margin: 2pt 0cm; line-height: 12.5pt;"><span style="font-family: 'Times New Roman','serif'; mso-ansi-language: EN-US;" lang="EN-US"><span style="font-size: small;"><span style="color: #585858;">Welding joints of stainless steels are in practice very sensitive places attacked by local corrosion, such as pitting and crevice corrosion, mostly in chloride containing oxidizing environments. It is caused by different oxidation products created on the surface by welding. Corrosion re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…Weld oxide referred to as heat tint is formed on the surface adjacent to the weld metal. The presence of heat tint has affected their corrosion resistance by microsegregation, precipitation of secondary phases, formation of unmixed zones, recrystallization, and grain growth in the weld heat-affected zone (HAZ) [13]. There are slight differences in the colors (yellow/brown/red/blue) depending on the steel grade and the heating method and conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Weld oxide referred to as heat tint is formed on the surface adjacent to the weld metal. The presence of heat tint has affected their corrosion resistance by microsegregation, precipitation of secondary phases, formation of unmixed zones, recrystallization, and grain growth in the weld heat-affected zone (HAZ) [13]. There are slight differences in the colors (yellow/brown/red/blue) depending on the steel grade and the heating method and conditions.…”
Section: Resultsmentioning
confidence: 99%
“…[14] The influence of surface roughness of SS and other metals and alloys on their resistance to pitting corrosion has been considered in a large number of papers. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] The roughness test results presented in these papers are often contradictory. Ezuber et al [15] have shown that resistance to pitting corrosion increases with decreasing surface roughness.…”
Section: Introductionmentioning
confidence: 99%